The European Foundation for Quality Management (EFQM) excellence model in a low voltage switchgear company - Özgür Özmen; Roxana Sârbu; Andreea Simona Săseanu; Corneliu Toader (Amfiteatru Economic Journal, 2017)
The Turkish low voltage switchgear sector is made up of several local and international companies. Generally, local companies operating in this sector try to get a competitive advantage by fabricating cheap products , in order to cope with the competition that focuses more on quality. What's more, international corporations perform quality activities under the organization and control of their top-managements from abroad. Although VIKO is a local producer, it is a company willing to invest more in quality, as well as in research and development. VIKO company is the focus of this self-assessment study, since it lies at the conjunction of companies operating in this sector, it being a local company performing various quality enhancement activities . Simultaneously, the authors consider that this study shall prove useful to create an overview over the entire Turkish low voltage switchgear sector. The evaluation of the company and its core-activities was based upon nine criteria of the European Foundation for Quality Management (EFQM) Excellence Model, in order to identify the strengths, the weaknesses and aspects that require improvements . This is the first study worldwide performed in the low voltage switchgear sector and it is aimed at motivating other Turkish companies that operate in this sector to implement The European Foundation for Quality Management (EFQM) Excellence Model in their TQM activities (Total Quality Management).
Keywords: L15; M16; M21; 330; self-assessment; The European Foundation for Quality Management (EFQM); low voltage switchgear sector